Multidimensional analyses of proinsulin peptide-specific regulatory T cells induced by tolerogenic dendritic cells. Issue 107 (February 2020) - Suwandi, Jessica S.; Laban, Sandra; Vass, Kincsὅ; Joosten, Antoinette; van Unen, Vincent; Lelieveldt, Boudewijn P.F.; Höllt, Thomas; Zwaginga, Jaap Jan; Nikolic, Tatjana; Roep, Bart O.
Abstract: Induction of antigen-specific regulatory T cells (Tregs) in vivo is the holy grail of current immune-regulating therapies in autoimmune diseases, such as type 1 diabetes. Tolerogenic dendritic cells (tolDCs) generated from monocytes by a combined treatment with vitamin D and dexamethasone (marked by CD52 hi and CD86 lo expression) induce antigen-specific Tregs. We evaluated the phenotypes of these Tregs using high-dimensional mass cytometry to identify a surface-based T cell signature of tolerogenic modulation. Naïve CD4 + T cells were stimulated with tolDCs or mature inflammatory DCs pulsed with proinsulin peptide, after which the suppressive capacity, cytokine production and phenotype of stimulated T cells were analysed. TolDCs induced suppressive T cell lines that were dominated by a naïve phenotype (CD45RA + CCR7 + ). These naïve T cells, however, did not show suppressive capacity, but were arrested in their naïve status. T cell cultures stimulated by tolDC further contained memory-like (CD45RA - CCR7 - ) T cells expressing regulatory markers Lag-3, CD161 and ICOS. T cells expressing CD25 lo or CD25 hi were most prominent and suppressed CD4 + proliferation, while CD25 hi Tregs also effectively supressed effector CD8 + T cells. We conclude that tolDCs induce antigen-specific Tregs with various phenotypes. This extends our earlier findings pointing to a functionally diverse pool of antigen-induced and specific Tregs and provides the basis for immune-monitoring in clinical trials with tolDC. Highlights: Tregs induced by tolDCs acquire distinct memory phenotypes with expression of Lag-3 and CD161. T cell lines stimulated with tolDCs retain naïve T cells that indirectly marks immune regulation. Low CD86 expression by tolDCs verifies their capacity to induce Tregs. TolDC-induced Tregs with both CD25 hi and CD25 lo memory phenotypes inhibit CD4 + T cell proliferation. CD25 hi memory Tregs also inhibit CD8 + T cell killing.